Standar Akuntansi Pemerintah Daerah dalam Rangka Transparansi Pelaporan Aktiva Tetap Pemerintah Daerah - Iriyadi, Iriyadi; Budiman, R. Aris (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2006)
The accounting standard of Regional Government forms accounting implementation standard to describe finance reporting as general goal in the frame of increasing sthe state of proportion of finance reporting either toward budget, inter-periodes, or inter-entities embracing acknowledgement, measurement, and disclosure of specific transactions from events in regional governmentâs finance accounting determined by Government Accounting Standard Commitee and in effect to the performance of regional governmentâs finance management. The finance Management of Bogor Regional Government manages bookkeeping on permanent assets of accounting departement. Bookkeeping starts from quating transactions in daily journal that will be made posting in the ledgerr, then it will be enclosed to finance accounting and fixed assets report of the Regional Government of Bogor Municipality. Keywords: Regional Governmentâs Accounting Standard; Regional Governmentâs Fixed Assets